Intimate partner violence against women and its association with pregnancy loss in Ethiopia: evidence from a national survey - Tenaw Yimer Tiruye; Catherine Chojenta; Melissa L. Harris; Elizabeth Holliday; Deborah Loxton (BMC, 2020)
Abstract Background Intimate partner violence (IPV) is major public health problem that affects many dimensions of women's health. However, the role of IPV on women's reproductive health in general and pregnancy loss in particular, is largely unknown in Ethiopia. Therefore, this study investigated the association between IPV and pregnancy loss in Ethiopia. Methods A retrospective analysis of nationally representative data from the 2016 Ethiopian Demographic and Health Survey (EDHS) was conducted. Married women of reproductive age (15-49 years) who participated in the domestic violence sub-study of the survey were included in the analysis. Adjusted odds ratios were estimated using multilevel logistic regression models to represent the association of IPV with outcome variable. Results Among 4167 women included in the analysis, pregnancy loss had been experienced by 467 (11.2%). In total, 1504 (36.1%) participants reported having ever experienced any form of IPV, with 25.1, 11.9, and 24.1% reporting physical, sexual and emotional IPV respectively. A total of 2371 (56.9%) women had also experienced at least one act of partner controlling behaviour. After adjusting for potential confounders, a significant association was observed between IPV (a composite measure of physical, sexual and emotional abuse) and pregnancy loss (Adjusted Odds Ratio (AOR) 1.54, 95% Confidence Interval (CI): 1.12, 2.14). The odds of pregnancy loss were also higher (AOR 1.72, 95% CI: 1.06, 2.79) among women who had experienced multiple acts of partner controlling behaviours, compared with women who had not experienced partner controlling behaviours. The intra-class correlation coefficient (ICC) indicated that pregnancy loss exhibits significant between-cluster variation (p < 0.001); about 25% of the variation in pregnancy loss was attributable to differences between clusters. Conclusion IPV against women, including partner controlling behaviour, is significantly associated with pregnancy loss in Ethiopia. Therefore, there is a clear need to develop IPV prevention strategies and to incorporate IPV interventions into maternal health programs.